Design and Implementation of a Multinational Computerized Patient Survey: The European Paediatric Orthopaedic Society Down Syndrome Survey - David M. Steinberg; Moshe Kaplan; Joav Merrick; Shlomo Wientroub (The Scientific World Journal)
In 1997, the European Paediatric Orthopaedic Society (EPOS) initiated an international survey of musculoskeletal problems in individuals with Down syndrome. The goals of the study were far-reaching and ambitious in order to obtain a clear picture of the variety of orthopedic problems associated with Down syndrome, to relate their occurrence to other medical conditions, and to record and compare methods of treatment. The survey was to be international in scope, including orthopedic surgeons and departments across Europe and outside Europe. The study was coordinated from the Tel Aviv University in Israel as a multicenter study using electronic technology. This paper describes the organization and implementation of the EPOS Down Syndrome Survey, with special emphasis on the sophisticated electronic data entry instrument that was developed especially for the survey. It is concluded that computerized data entry forms like the one that we developed for the EPOS Down Syndrome Survey are valuable tools for medical surveys. They are especially important for multicenter and multinational studies.